Alternative access in transcatheter aortic valve replacement—an updated focused review - Abdelnour, Mark W.; Patel, Vishal; Patel, Pranav M.; Kasel, A. M.; Frangieh, Antonio H. (Frontiers in Cardiovascular Medicine, 2024)
Aortic Stenosis (AS) is a common condition with an estimated pooled prevalence of all AS in the elderly population at around 12.4%, with that of severe AS estimated to be around 3.4%. In the past, surgical aortic valve replacement was the primary treatment option for severe AS for decades. However, with the compelling evidence on the safety and efficacy of transcatheter aortic valve replacement (TAVR), it has become the gold standard treatment option for many patients with symptomatic severe AS. Transfemoral access has been the preferred method for transcatheter heart valve delivery. However, the prevalent use of TAVR on a diverse patient profile with different risk factors, such as peripheral artery disease, precluded the possibility of a transfemoral approach despite the improvement of valves and delivery systems technology. Therefore, alternative TAVR approaches have gained increasing utility in cases where transfemoral access is unfavorable. We review the journey, evolution, and techniques for different approaches of percutaneous TAVR, including transfemoral, transcarotid, transsubclavian/transaxillary, and transcaval approaches, in addition to the traditional “surgical” transaortic and transapical accesses. Consolidating these data highlights each approach's practicality and limitations, providing additional grounding for case-by-case utilization and future clinical research.